The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18257/raccefyn.1305
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad y estructura de los ensamblajes ícticos en los humedales, caños y esteros de la sabana inundable del río Ariporo, Casanare, Colombia

Abstract: Las sabanas inundables son un bioma importante para la diversidad y funcionalidad de lascomunidades ícticas del Orinoco. Estas sabanas tienen gran conectividad y diversidad ecosistémica,incluida la conformación de diferentes tipos de humedales, por lo que comprender la forma en quesus comunidades de peces se estructuran en los diversos ambientes es clave para la conservaciónbiológica. El objetivo de este estudio fue determinar la diversidad, la composición y la estructura delos ensamblajes ícticos en los humed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Additionally, the proximity of the sampling stations and the stability of the physicochemical conditions of the water, allow a constant change of species along the stream. This finding is consistent with what was observed by Sánchez, Castro, Galvis, (1996) and Ospina-O et al (2021), who found no changes in fish richness at a temporal level, for some rivers and wetlands of the Casanare and Meta floodplains. Regarding the diversity of order q = 1 and 2, it was found that the high-water period presented the highest values of common and dominant species, this behavior could be attributed to the increase in abundance of some species found in larval and juvenile stages, as is the case of Agamyxis albomaculatus, Amblydoras gonzalezi, Apistogramma hongsloi, Astyanax aff.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the proximity of the sampling stations and the stability of the physicochemical conditions of the water, allow a constant change of species along the stream. This finding is consistent with what was observed by Sánchez, Castro, Galvis, (1996) and Ospina-O et al (2021), who found no changes in fish richness at a temporal level, for some rivers and wetlands of the Casanare and Meta floodplains. Regarding the diversity of order q = 1 and 2, it was found that the high-water period presented the highest values of common and dominant species, this behavior could be attributed to the increase in abundance of some species found in larval and juvenile stages, as is the case of Agamyxis albomaculatus, Amblydoras gonzalezi, Apistogramma hongsloi, Astyanax aff.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, one of the challenges of ecology and conservation biology is to understand the factors that determine the richness, abundance, and distribution of species in megadiverse regions (Arrington and Winemiller, 2005), due to the crisis of biodiversity loss produced by anthropogenic impacts (Cardinale et al, 2012;Montoya-Ospina, López-Delgado, Hevia, Villa-Navarro, 2020). For the Colombian Orinoquia, most of the studies on fish communities have focused on the surveying (Urbano-Bonilla et al, 2009;Ramírez-Gil et al, 2011;Villa-Navarro et al, 2011;Maldonado-Ocampo et al, 2013;Urbano-Bonilla et al, 2014;Usma et al, 2016;Zamudio et al, 2017;Urbano-Bonilla et al, 2018), and a few studies have focused on fish assemblages, based on habitat structural complexity (Montoya-Ospina et al, 2020;Lasso et al, 2021) and temporality (Ospina-O, Bedoya-Giraldo, Villa-Navarro, 2021). Therefore, the objective of this study was to describe the fish assemblage of the Mitimiti stream and test the hypothesis that they vary at a spatial and temporal level.…”
Section: Introductionmentioning
confidence: 99%